Minority Status and the Use of Computer-Mediated Communication: A Test of the Social Diversification Hypothesis. - Mesch, Gustavo S. (Communication Research, 2012)
Group differences in the use of computer-mediated communication (CMC) were investigated, to test the diversification hypothesis that argues that minorities and immigrants will be more likely to use CMC to compensate for their lack of social capital. Data were gathered from a sample of Internet users reflecting the percentage of minorities in the general population (n = 1,264). The results provide support for the hypothesis, indicating that in multicultural societies disadvantaged groups show greater motivation to use CMC to expand business and occupational contacts, whereas members of the majority group are more motivated to use CMC to maintain existing family and friendships ties. Implications of the finding are discussed.